Prospective, Controlled, Multicentre Study of Loperimide in Pregnancy - A Einarson; P Mastroiacovo; J Arnon; A Ornoy; A Addis; H Malm; G Koren (Canadian Journal of Gastroenterology)
BACKGROUND: Loperamide is a synthetic piperidine derivative used for the treatment of both acute and chronic diarrhea. Little is known about its safety and risk in pregnancy. Human data are limited to one surveillance study of Michigan Medicaid patients, with 108 women exposed in the first trimester. In this study there were six major birth defects, three of which were cardiovascular anomalies.